Das grafias rascunhadas da ditadura à construção de um espaço do saber: a importância da UNIOESTE nas transformações sociais da cidade de Cascavel - PR - Royer, Gean Carlos (2021)
One of the most recurring assertions, when analyze the social effects brought by higher education institutions, is the one that point to the effective role in the fomentation of national improvement. However, the studies of the impacts brought by these institutions for the local and regional improvement are still incipient. In this perspective, this dissertation’s objective is to analyze the foundation importance of the Universidade Estadual do Oeste do Paraná - UNIOESTE to the social, politic, cultural and economic transformations which its city, Cascavel, in Paraná, had passed and still does. So, based in the descriptive method, this research examine the impact of the regional changes in the educational tactics and, to the same extend, analyze the multiple determinations between social space and the nature of public higher education offered. Therefore, the investigation and historiography check that the education is one of the larger factors to the social transformation, bearing in mind that this one acts on the people, and these, on the other hand, transform the local in pursuit of a better life quality and of material life. It was noticed, in this research, that the arrays facing the formation of the higher education derive from the Europe models, mainly from Portuguese, given the historical relationship Metropolis-Colony, but also by the incorporation of others Europe and North-American models throughout the 20th century. It was also observed that both the formation of the Unioeste and the construction of the University Hospital were only possible because mobilization and claim from various sectors of the Cascavel’s society, giving the need of a public higher education institution and, simultaneously, of a public hospital. Lastly, it was concluded that the Unioeste, Cascavel campus, along with the University Hospital, were and are valuable institutions in the scope of the transformations that have occurred in this town, reflecting in the local and regional improvement either form the perspective of professional formation, intellectualized/qualification of the population, or from the perspective of health care provided by the physiotherapy and odontology clinics in the Cascavel campus or in the Hospital Universitário do Oeste do Paraná.